Effect of four different forms of high intensity training on BDNF response to Wingate and Graded Exercise Test - Murawska-Ciałowicz, Eugenia; de Assis, Gilmara Gomes; Clemente, Filipe Manuel; Feito, Yuri; Stastny, Petr; Zuwała-Jagiełło, Jolanta; Bibrowicz, Bartosz; Wolański, Paweł (Scientific reports, 2021)
This study examined the effects of a nine-week intervention of four different high-intensity training modalities [high-intensity functional training (HIFT), high-intensity interval training (HIIT), high-intensity power training (HIPT), and high-intensity endurance training (HIET)] on the resting concentration of brain-derived neurotropic factor (BDNF). In addition, we evaluated the BDNF responses to Graded Exercise Test (GXT) and Wingate Anaerobic Test (WAnT) in men. Thirty-five healthy individuals with body mass index 25.55 ± 2.35 kg/m2 voluntarily participated in this study and were randomly assigned into four training groups. During nine-weeks they completed three exercise sessions per week for one-hour. BDNF was analyzed before and after a GXT and WAnT in two stages: (stage 0-before training and stage 9-after nine weeks of training). At stage 0, an increase in BDNF concentration was observed in HIFT (33%; p < 0.05), HIPT (36%; p < 0.05) and HIIT (38%; p < 0.05) after GXT. Even though HIET showed an increase in BDNF (10%) this was not statistically significant (p > 0.05). At stage 9, higher BDNF levels after GXT were seen only for the HIFT (30%; p < 0.05) and HIIT (18%; p < 0.05) groups. Reduction in BDNF levels were noted after the WAnT in stage 0 for HIFT (- 47%; p < 0.01), HIPT (- 49%; p < 0.001), HIET (- 18%; p < 0.05)], with no changes in the HIIT group (- 2%). At stage 9, BDNF was also reduced after WAnT, although these changes were lower compared to stage 0. The reduced level of BDNF was noted in the HIFT (- 28%; p < 0.05), and HIPT (- 19%;p < 0.05) groups. Additionally, all groups saw an improvement in VO2max (8%; p < 0.001), while BDNF was also correlated with lactate and minute ventilation and selected WAnT parameters. Our research has shown that resting values of BDNF after nine weeks of different forms of high-intensity training (HIT) have not changed or were reduced. Resting BDNF measured at 3th (before GXT at stage 9) and 6th day after long lasting HITs (before WAnT at stage 9) did not differed (before GXT), but in comparison to the resting value before WAnT at the baseline state, was lower in three groups. It appears that BDNF levels after one bout of exercise is depended on duration time, intensity and type of test/exercise.
Keywords: Brain-Derived Neurotrophic Factor; mozkový neurotrofický faktor; zátěžový test; Rest; Adult; dospělí; Exercise; vysoce intenzivní intervalový trénink; Humans; mužské pohlaví; Male; cvičení; index tělesné hmotnosti; lidé; Body Mass Index; Exercise Test; odpočinek; High-Intensity Interval Training